APPLICATION OF MEMBRANE TECHNOLOGY ON FOOD GRADE FOOD CONCENTRATE PRODUCTION FROM PANDAN LEAVES - Lutfan Akbar, Muhammad
Pandan green paste and colorant, as one of the additives with the largest use in the food industry, are generally made from synthetic materials. This is due to the practicality of the production process, relatively low production costs, and generally better color quality provided by the product. However, the trend shift towards the consumption of more natural food products has increased the sales opportunities for natural food colorant. Pandan leaves contain chlorophyll that gives its signature green color. There have been many practices of natural pandan paste production at homes for personal consumption, but it generally does not go through a process of concentration so that the pandan paste is generally more fluid and can significantly affect the characteristics of the final food product. One method of concentration that can be done is with Osmotic Membrane Distillation (OMD). This research study aims to find the optimal conditions for the extraction of chlorophyll from pandan and their concentration process using OMD. This research will be conducted by extracting pandan using water and propylene glycol (PG) mixture as the solvent with the mass ratio of pandan to solvent equals to 1 : 4 for 2 and 12 hours. The PG content in the solvent will be varied from 0%, 20%, 40%, 60%, 80%, and 100%. Concentration with OMD by submerged direct contact membrane distillation (SDCMD) for 3 hours with the flow rates of Osmotic Agent (OA) were 1 and 1,5 mL/s at 35°C and atmospheric pressure. The color of the extract will be tested using a spectrophotometer to determine the chlorophyll content. The product of the concentration process, which are the supernatant and the permeate, will be analysed to determine the performance of the concentration process. The chlorophyll content, color profile, viscosity, and the dispersibility of the supernatant in water will be analysed. The existence of pandan aroma and the PG content of the permeate will be analysed.